Anthrone and oxanthrone C,O-diglycosides from Picramnia teapensis - Rodriguez-Gamboa, T.; Victor, SR; Fernandes, J. B.; Fo, E. R.; da Silva, MFDF; Vieira, P. C.; Pagnocca, F. C.; Bueno, O. C.; Hebling, MJA; Castro, O. (Elsevier B.V., 2000)
Two C,O-diglycosylated compounds, the anthrone picramnioside F, and the oxanthrone mayoside C, were isolated from the stem bark of Picramnia teapensis, along with the previously reported anthraquinones, 1-O-beta -D- and 8-O-beta -D-glucopyranosyl emodin. The compounds were separated by recycling-HPLC, and their structures were determined on the basis of spectroscopic analysis. CD measurements were used to establish the absolute configuration of the anthrone and oxanthrone. The antifungal activity of 1-O-beta -D- and 8-O--D-glucopyranosyl emodin against Leucoagaricus gongilophorus was shown to be similar to that of the lignan sesamin. (C) 2000 Elsevier B.V. Ltd. All rights reserved.
Keywords: Picramnia teapensis; Simaroubaceae; anthraquinone glycosides; anthrone glycoside; oxanthrone glycoside; picramnioside; mayoside; antifungal activity